Long term ex vivo culturing of Drosophila brain as a method to live image pupal brains: insights into the cellular mechanisms of neuronal remodeling - Rabinovich, Dana; Mayseless, Oded; Schuldiner, Oren (Frontiers in Cellular Neuroscience, 2015)
Holometabolous insects, including Drosophila melanogaster, undergo complete metamorphosis that includes a pupal stage. During metamorphosis, the Drosophila nervous system undergoes massive remodeling and growth, that include cell death and large-scale axon and synapse elimination as well as neurogenesis, developmental axon regrowth and formation of new connections. Neuronal remodeling is an essential step in the development of vertebrate and invertebrate nervous systems. Research on the stereotypic remodeling of Drosophila mushroom body (MB) γ neurons has contributed to our knowledge of the molecular mechanisms of remodeling but our knowledge of the cellular mechanisms remain poorly understood. A major hurdle in understanding various dynamic processes that occur during metamorphosis is the lack of time-lapse resolution. The pupal case and opaque fat bodies that enwrap the central nervous system (CNS) make live-imaging of the central brain in-vivo impossible. We have established an ex-vivo long-term brain culture system that supports the development and neuronal remodeling of pupal brains. By optimizing culture conditions and dissection protocols, we have observed development in culture at kinetics similar to what occurs in vivo. Using this new method, we have obtained the first time-lapse sequence of MB γ neurons undergoing remodeling in up to a single cell resolution. We found that axon pruning is initiated by blebbing, followed by one-two nicks that seem to initiate a more widely spread axon fragmentation. As such, we have set up some of the tools and methodologies needed for further exploration of the cellular mechanisms of neuronal remodeling, not limited to the MB. The long-term ex-vivo brain culture system that we report here could be used to study dynamic aspects of neurodevelopment of any Drosophila neuron.